The Relative Costs of High- vs. Low-Energy-Density Foods and More vs. Less Healthful Beverages Consumed by Children. Issue 2 (3rd April 2018) - Evans, Kristin; Stewart, Patricia; Cook, Stephen; Seplaki, Christopher; Rich, David; Fernandez, I.
ABSTRACT: The objective of this study was to compare grocery costs between relatively high-energy-density foods and sugar-sweetened/high-fat beverages and lower energy-density foods and more healthful beverages in children's diets. Sixty foods were divided into high- and low-energy-density baskets. Fourteen beverages were designated to either basket based on fat and added-sugar content. Prices were collected at 60 grocery stores and composite costs compared between baskets using Wilcoxon tests. The cost per kilogram of high-energy-density foods was greater, but the cost per quart of sugar-sweetened/high-fat beverages was lower than more healthful beverages. The cost per 1000 calories and the cost per serving of the high-energy-density basket were lower. The relative cost of high- and low-energy-density foods in children's diets depends on how cost is quantified. "Pound-for-pound, " lower energy-density foods and more healthful beverages are generally less expensive, but high-energy-density foods and less healthful beverages are cheaper per serving. Cost metrics including other factors (eg, time cost) may further clarify the role of grocery prices in children's diets.